2021
DOI: 10.1093/jscr/rjab228
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer crystals—an unusual cause of large bowel obstruction

Abstract: Sevelamer is a common phosphate binder used to manage hyperphosphatemia in end-stage renal disease. The medication has a well-documented gastrointestinal side-effect profile including nausea, vomiting and abdominal pain. There are few case reports of Sevelamer crystal deposition causing gastrointestinal mucosal injury, pseudotumor or obstruction. Here, we discuss a patient on Sevelamer who required operative management of a sigmoid obstruction. Surgical pathology showed pericolonic abscess with Sevelamer cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
3
0
2
Order By: Relevance
“…In another report, a bezoar of sevelamer crystals was implicated in intestinal obstruction, but notably was at the site of a pre‐existing stricture 19 . Similar to our findings, sevelamer has been previously reported in perforated diverticula 5 . Others attribute GI bleeding to sevelamer in patients immediately after heparin infusions or initiation of haemodialysis 20,21 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In another report, a bezoar of sevelamer crystals was implicated in intestinal obstruction, but notably was at the site of a pre‐existing stricture 19 . Similar to our findings, sevelamer has been previously reported in perforated diverticula 5 . Others attribute GI bleeding to sevelamer in patients immediately after heparin infusions or initiation of haemodialysis 20,21 .…”
Section: Discussionsupporting
confidence: 88%
“…19 Similar to our findings, sevelamer has been previously reported in perforated diverticula. 5 Others attribute GI bleeding to sevelamer in patients immediately after heparin infusions or initiation of haemodialysis. 20,21 Conversely, a review of 16 reported cases by Yuste et al noted that sevelamer associated gastrointestinal injury was frequently seen in association with disorders that impair intestinal motility, such as diabetes mellitus (63%) or history of major intra-abdominal surgery (38%), but did not note an association with dose of sevelamer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kendte hyppige bivirkninger ved colestyraminbehandling omfatter abdominalsmerter, diarré og obstipation. Ionbytterpraeparater kan i sjaeldne tilfaelde forårsage krystalaflejringer i gastrointestinalkanalen [1], hvilket kasuistisk er beskrevet som mulig årsag til inflammation, blødning fra mave-tarm-kanalen og undtagelsesvist nekrose og perforation [2][3][4][5].…”
unclassified